A Guideline for Academic Administration in Learning Process Anagement Through The ONIE MODEL at Doi Lor District Learning Encouragement Center, Chiang Mai Province - Chaiboot, Napaporn; Pakdee, Chalee; Mahavīro, Asst. Prof. Dr., Phramaha Sakun (MCU Haripunchai Review, 2025)
The objectives of this research were: 1. To study the current conditions of Academic Administration in learning process management using the ONIE Model at the Doi Lor District Learning Promotion Center, Chiang Mai Province; and 2.To identify guidelines for academic administration in learning process management using the ONIE Model at the same center. This was qualitative research. The target group consisted of six participants, including the director and government employees. The research instruments were an interview form and a group discussion record. Data were analyzed using content analysis. The results of the research found that: 1) The current state of academic administration at the Doi Lor District Learning Promotion Center revealed the use of the ONIE Model for managing the learning process, which involves jointly identifying problems and needs, seeking information and new learning, applying knowledge in practice, and evaluating learning outcomes. The process was improved to match learners’ needs and current situations. However, weaknesses were identified in terms of limited budget and personnel. 2) The guidelines for academic administration in learning process management using the ONIE Model suggested that this model is suitable for non-formal education. It should integrate community needs and establish an evaluation system that reflects actual outcomes. It is recommended to use group discussions to identify community problems and needs, as well as information technology and participatory learning, to achieve sustainable results. This research emphasizes integrating community needs into an appropriate learning process and creating an evaluation system that reflects real performance to ensure sustainability.